Excavating with cows - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
For several years now, ILCA (International Livestock Centre for Africa) has been successfully experimenting with the use of draught animal power to excavate ponds. A pair of cows harnessed to an easily made implement can move 13 cubic metres of...